Airborne Spread of SARS-CoV-2 Between Rooms in a Sealed, Mechanically Ventilated Ward: Evidence from a Hospital Outbreak Investigation - Yo Ishigaki (11052900) (2025)
Introduction: Airborne transmission of SARS-CoV-2 within enclosed, mechanically ventilated hospital wards remains insufficiently characterized. In February 2025, a COVID-19 cluster involving 17 individuals (12 patients, 4 nurses, 1 cleaner) occurred across multiple rooms of a sealed general ward in a mid-sized Japanese hospital. Several infected individuals had no documented close contact with the index patient, raising concern for inter-room aerosol transmission driven by ventilation-related airflow. Methods: A multi-modal environmental investigation was conducted using three complementary approaches: (1) CO2 decay experiments to quantify air change rates (ACH), (2) PM2.5 aerosol dispersion measurements using fog as a surrogate tracer, and (3) Computational Fluid Dynamics (CFD) simulations to visualize airflow and scalar transport. Measurements were obtained in Room A (index case location), the shared corridor, and adjacent Rooms B–D. Experiments compared closed-door and open-door conditions, and CFD modeling reproduced the actual mechanical ventilation configuration. Results: Opening the patient-room door significantly increased the indoor ACH (3.29/h → 4.01/h, p = 0.030), while also allowing CO2 tracer gas to escape into the corridor. In the PM2.5 dispersion experiment, particles released in Room A were detected not only within the room but also in the corridor and in neighboring rooms, with the highest out-of-room particle burden observed at the corridor sensor (AUC = 3.1 × 106 μg·s/m3). PM2.5 and PM10 concentrations were strongly correlated (r = 0.9997), indicating the presence of intermediate-sized particles capable of longer-range transport. CFD simulations reproduced key qualitative features of the experiments, including accumulation of tracer within curtain-enclosed compartments, delayed leakage through the doorway, and downstream transport toward the corridor. Conclusion: This integrated assessment demonstrates that inter-room aerosol transport can occur in a sealed, mechanically ventilated ward, even without natural ventilation or structural openings between rooms. Opening doors improves in-room ventilation but simultaneously promotes aerosol escape, revealing a trade-off between dilution and contamination of shared spaces. Architectural elements such as privacy curtains further contribute to airflow stagnation and uneven aerosol removal. Effective infection-control strategies must therefore incorporate airflow-pathway management and localized filtration to prevent unintended aerosol migration in mechanically ventilated healthcare settings.